Voltage Stability Based Formation of Voltage Control Areas Considering Impact of Contingencies - Tarun Martolia; M.K. Verma (Institute of Advanced Engineering and Science, 2012)
Voltage instability has been considered as a major threat to power system networks since last three decades. Frequent incidences of grid failures caused by voltage instability have been observed in different parts of the world. Fast voltage stability assessment of power system may be done by formation of voltage control areas, clubbing group of buses in geographically compact region having similar voltage instability problem. This paper presents a new approach for formation of voltage control areas (VCAs) based on sensitivity of reactive power generations with respect to reactive power demands, together with bus voltage variations under voltage stability based critical contingencies. The load buses in geographically compact region showing similar sensitivity of reactive power demand to reactive generations have been clubbed together to form voltage control areas. Since, voltage control areas formed should remain valid under change in operating conditions and network topology, the areas formed based on reactive power sensitivitieshave been modified considering voltage variations at different loadings points under voltage stability based critical contingencies. Voltage stability based Critical contingencies have been selected based on maximum loadability criterion. Case studies have been performed on IEEE 14-bus system. Simulation results performed on IEEE 14-bus system validate VCAs formed even under change in network topology caused by line outages and change in operating conditions caused by variations in real and reactive power demands. The VCAs formed by proposed method have been compared with VCAs formed by few existing approaches. The superiority of proposed approach of voltage control areas formation over few existing approaches has been established on the test system considered.